2016
DOI: 10.1038/hdy.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of chromosome segments from multiple alien species in wheat breeding lines with wheat streak mosaic virus resistance

Abstract: Pyramiding of alien-derived Wheat streak mosaic virus (WSMV) resistance and resistance enhancing genes in wheat is a costeffective and environmentally safe strategy for disease control. PCR-based markers and cytogenetic analysis with genomic in situ hybridisation were applied to identify alien chromatin in four genetically diverse populations of wheat (Triticum aestivum) lines incorporating chromosome segments from Thinopyrum intermedium and Secale cereale (rye). Out of 20 experimental lines, 10 carried Th. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 41 publications
(83 reference statements)
0
32
0
1
Order By: Relevance
“…The role of presynaptic centromere associations and their transition to homologous pairing Individual chromosome pairs visualized by in situ hybridization (Schwarzacher et al, 1992) can be studied in alien introgression lines of hexaploid wheat, carrying whole chromosomes or chromosome arms from a related species (Moln ar et al, 2015;Ali et al, 2016). A study on a wheat-rye translocation line revealed that cognition of homologous chromosome partners initiates at the centromeres in meiotic interphase and, subsequently, homologous chromosome segments align in leptotene with synapsis starting at the telomeres (Schwarzacher, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The role of presynaptic centromere associations and their transition to homologous pairing Individual chromosome pairs visualized by in situ hybridization (Schwarzacher et al, 1992) can be studied in alien introgression lines of hexaploid wheat, carrying whole chromosomes or chromosome arms from a related species (Moln ar et al, 2015;Ali et al, 2016). A study on a wheat-rye translocation line revealed that cognition of homologous chromosome partners initiates at the centromeres in meiotic interphase and, subsequently, homologous chromosome segments align in leptotene with synapsis starting at the telomeres (Schwarzacher, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Selection may be related to agronomic performance and also regional use differences (Worku et al 2005(Worku et al , 2012. Previously, Ali et al (2016) showed clusters of variation between the Ethiopian linseed landraces and non-native cultivars for majority of morphological traits. Noormohammadi et al (2015) reported wild L. austriacum L. populations at intermediate altitudes have greater diversity than populations at lower and higher altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 102 PCR-based markers were applied aiming to understand their genetic structure and to identify molecular markers that are closely associated to quantitative trait loci (QTLs) of important root traits ( Table 2). Plant germination, DNA extraction and PCR proiling followed previously published standard procedures [32]. Further, population structure of these lines was analyzed with general linear model (GLM) and mixed linear model (MLM) approaches using TASSEL software with their default seting for identiication of QTLs associated with important root traits.…”
Section: Methodsmentioning
confidence: 99%